Margetuximab Versus Trastuzumab in Patients With Previously Treated HER2-Positive Advanced Breast Cancer (SOPHIA): Final Overall Survival Results From a Randomized Phase 3 Trial. Issue 2 (4th November 2022) - Rugo, Hope S.; Im, Seock-Ah; Cardoso, Fatima; Cortes, Javier; Curigliano, Giuseppe; Musolino, Antonino; Pegram, Mark D.; Bachelot, Thomas; Wright, Gail S.; Saura, Cristina; Escrivá-de-Romaní, Santiago; De Laurentiis, Michelino; et al.
Abstract : Clinical trials frequently include multiple end points that mature at different times. The initial report, typically based on the primary end point, may be published when key planned co-primary or secondary analyses are not yet available. Clinical Trial Updates provide an opportunity to disseminate additional results from studies, published in JCO or elsewhere, for which the primary end point has already been reported. Final overall survival (OS) in SOPHIA (ClinicalTrials.gov identifier: NCT02492711 ), a study of margetuximab versus trastuzumab, both with chemotherapy, in patients with previously treated human epidermal growth factor receptor 2–positive advanced breast cancer, is reported with updated safety. Overall, 536 patients in the intention-to-treat population were randomly assigned to margetuximab (15 mg/kg intravenously once every 3 weeks; n = 266) plus chemotherapy or trastuzumab (6 mg/kg intravenously once every 3 weeks after a loading dose of 8 mg/kg; n = 270) plus chemotherapy. Primary end points were progression-free survival, previously reported, and OS. Final OS analysis was triggered by 385 prespecified events. The median OS was 21.6 months (95% CI, 18.89 to 25.07) with margetuximab versus 21.9 months (95% CI, 18.69 to 24.18) with trastuzumab (hazard ratio [HR], 0.95; 95% CI, 0.77 to 1.17; P = .620). Preplanned, exploratory analysis of CD16A genotyping suggested a possible improvement in OS for margetuximab in CD16A-158FF patients versus trastuzumab (median OS, 23.6 v 19.2 months; HR, 0.72; 95% CI, 0.52 to 1.00) and a possible improvement in OS for trastuzumab in CD16A-158VV patients versus margetuximab (median OS, 31.1 v 22.0 months; HR, 1.77; 95% CI, 1.01 to 3.12). Margetuximab safety was comparable with trastuzumab. Final overall OS analysis did not demonstrate margetuximab advantage over trastuzumab. Margetuximab studies in patients with human epidermal growth factor receptor 2–positive breast cancer with different CD16A allelic variants are warranted.